For eco-social market economy instead of post-communist capitalism - Jakovljević, Dragan (Napredak, 2022)
This essay presents and considers the vision of eco-social market economy as a possible basis for upgrading the socio-economic order in Serbia. It is the so-called middle road (between state socialism and rigid liberalism of deregulated markets), i.e., “mixed economy”, whose formation has been given key enticements by the Christian heritage of the European countries. The author illustrates it particularly on the example of the experience of the so-called German economic miracle after the collapse in the Second World War – which led to the building of one of the most stable economies in the modern world. The historical genesis of that concept is presented, the application of which culminated in the economic systems of the Scandinavian countries, Germany, Austria etc. in the late 20th century. Moreover, the aspiration towards social security, solidarity and fairness implies a certain redistribution of economic goods, i.e., realized profits by the state. The author sees this system solution as a reconciliating formula that, while keeping the affirmation of market efficiency of business operations and freedom of entrepreneurship, also insists on effective institutionalization of social, as well as ecological consideration.